Pengaruh Etika Profesi, Pengalaman Auditor dan Independensi Terhadap Kinerja Auditor Pada Kantor Akuntan Publik di Kota Medan - Aurani Raodah; Hafsah Hafsah (Politeknik Ganesha Medan, 2023)
This study aims to determine the effect of professional ethics, auditor experience and independence on auditor performance at the Public Accounting Firm in Medan City. In this study the authors used an associative approach, the data source used was primary data. The data collection technique used was by distributing questionnaires to 173 auditors working at the Public Accounting Firm in Medan City. The sampling technique used is saturated sampling. The data analysis technique used to test the hypothesis in this study is Multiple Linear Regression Analysis using Statistical Package for the Social Sciences (SPSS) version 25. The results of this study indicate that 1) Professional Ethics has a positive and significant effect on Auditor Performance, 2) Experience The auditor has no significant effect on the performance of the auditor, 3) Independence has a significant effect on the performance of the auditor, 4) Independence has a positive and significant effect on the performance of the auditor and professional ethics, experience of the auditor and independence simultaneously and has a significant effect on the performance of the auditor.